Unsur-unsur pendidikan - Khusnah, Ema Ummiyatul (Maliki Interdisciplinary Journal, 2024)
The elements of education are key components in effective learning processes. Educational objectives provide direction, while content encompasses relevant learning materials. Teaching methods determine the way information is delivered, and assessment measures goal achievement. The learning environment plays a role in creating a positive learning context, and educators have a central role in guiding learners. The harmonious integration of these elements is crucial in developing impactful and holistic education.